Quantifiers as evidence of the language of uncertainty: A psycholinguistic approach - Bazán Guzmán, Jorge Luis (2006)
A theoretical approach is presented to study the quantifiers like evidence of the languageof uncertainty. The following topics are considered: language and uncertainty, probabilistic reasoning, learning and evaluation of the quantifiers, and the study of the quantifiers like study of the meaning and the understanding of words, which constitutes the psycholinguis- tics of the quantifiers. We argue that the quantifiers, as words, are part of the language of uncertainty that is part of the probabilistic reasoning, but the mechanism of its learning is not known. We also consider that it is important to locate the study of the quantifiers within the study of the meaning as evidence of internal psychological processes. Future investigatio-ns will facilitate a better understanding of the use of the quantifiers.